Multiplug safety portable - Norazah binti Mustaffa (Department of Electronic Engineering Technology, Faculty of Engineering Technology, University Malaysia Perlis, 2015)
This project is focused on the upgraded multiplug which is more efficient compared to existing multiplug. This project is design to give double protections toward socket system that is connecting in grouping and individually. As the day by day, people find out that uses of electrical become huge and nobody can live without it. This multiplug safety portable box is being planned according to latest requirement in order to protect the main switch when the short circuit occur. So it help the user to known when the fault current happen then the user can take action immediately. The problem arise from multiplug safety extension are the disruption of main switch during short circuit, user become difficult and the houses is not protected. In addition, the objective of this project to design single phase double protection toward socket system and upgrade the common extension to multiplug safety portable box. Besides that, the project concerned the user to monitor maximum load and be careful to exceed. Furthermore, the multiplug safety portable box is planned to protect the houses during short circuit and to handle using multitypes of plug without need to get add on socket or header to used it. Finally, to accomplish this project, it must make the planning and flow chart.